Blake’s Virtual Designs and Reconstruction of The Song of Los - Viscomi, Joseph (Romanticism on the Net, 2006)
AbstractIn this essay, I realize digitally the virtual designs that Blake evokes in The Song of Los and other illuminated books. Blake’s virtual designs are designs we create mentally by recombining an illuminated book’s related images. By visualizing mental images concretely, we reify the experiences of memory and imagination, comparison and contrast, that we employ when reading/seeing Blake's works. Moreover, by doing so, we engage in creative processes involving memory and imagination similar to Blake's own when inventing new designs from elements of others. I also realize digitally the original horizontal designs for Blake's “Africa” and “Asia” in The Song of Los before they were altered in printing. As originally executed, each poem functioned autonomously, with text superimposed on a landscape design. Digital recreations demonstrate how radically Blake fused poetry, painting, and printmaking, creating panels, broadsides, or scrolls rather than book pages, and how Song of Los, as printed, was Blake’s attempt to reconstruct an experiment about which he had changed his mind.